Stress Degradation Studies of Riociguat, Development of Validated Stability Indicating Method, Identification, Isolation and Characterization of Degradation Products by LC-HR-MS/MS and NMR Studies - Pandya, Charu P; Rajput, Sadhana J (Indian Journal of Pharmaceutical Education and Research, 2019)
Aim: The present study reports the degradation behavior of new antihypertensive drug Riociguat under various stress conditions as per International Conference on Harmonization guidelines ICH, Q2(R1). Materials and Methods: Riociguat was subjected to stress degradation under hydrolytic (acidic, alkaline and neutral), oxidative, photolytic and thermal stress conditions to investigate the inherent stability. A rapid, accurate, precise and robust HPLC method was developed on Waters Symmetry C18 Column (150mm X 4.6 mm, 5µ) using isocratic elution of 10 mm ammonium acetate buffer pH 5.7 and acetonitrile in the ratio of 70:30 with the flow rate at 1.0 mL/min.The detection was performed at 254nm. Results: The drug was found to be degraded in alkaline and oxidative condition whereas it was stable under acidic, neutral hydrolytic, thermal and photolytic conditions. Two degradation products (DP1, DP2) under alkaline condition and one under oxidative condition (DP3) were characterized by LC-HR-MS/MS with accurate mass measurements. Degradation products (DP1, DP2 and DP3) were isolated by preparative HPLC and were characterized by 1H NMR, 13C NMR, APT and IR Techniques. Conclusion: Using spectral data analysis, alkaline degradation product DP1 wascharacterized as 2-(1-(2-fluorobenzyl)-1H-pyrazolo[3,4-b]pyridin-3-yl)-N5-methylpyrimidine-4,5,6-triamine and DP2 was characterized as 2-(1-(2-fluorobenzyl)-1H-pyrazolo[3,4-b]pyridin-3-yl)- 6-amino-7-methyl-7H-purin-8(9H)-one while oxidative degradation product DP3was characterized as methyl 2-(1-(2-fluorobenzyl)-1H-pyrazolo[3,4-b]pyridin-3-yl)-4,6- diaminopyrimidin-5-ylmethylcarbamate-N-oxide.The developed chromatographic method was validated in terms of specificity, linearity, accuracy, precision as per ICH guidelines. The robustness of the method was studied with 2-level fractional factorial design 2^4-1.
Keywords: Riociguat; Stress degradation; RP-HPLC; LC-HR-MS/MS; Preparative HPLC; NMR